Variabel-Variabel yang Memengaruhi Kejadian Diare pada Balita di Provinsi Jawa Barat Tahun 2023 - Chairunnisa, Tiara; Sukim, Sukim (Politeknik Statistika STIS, 2025)
Diarrhea remains one of the leading communicable diseases contributing to under-five mortality. According to the Ministry of Health 2023, West Java Province ranked third nationally and first on the island of Java in terms of diarrhea prevalence among children under-five, with a rate of 11%. This phenomenon is associated with high population density and limited access to proper sanitation. This study aims to describe the incidence of diarrhea among children under five and analyze several variables affecting diarrhea incidence in West Java, using data from SKI 2023. The analysis was conducted using binary logistic regression. The findings show that child age, maternal education, and household sanitation are associated with diarrhea incidence in under five children in West Java. It is recommended that the West Java local government focus its diarrhea prevention programs on children aged 6-23 months, provide health education especially mother, and ensure adequate sanitation facilities in every household.